Gambogic acid triggers vacuolization-associated cell death in cancer cells via disruption of thiol proteostasis - Seo, Min Ji; Lee, Dong Min; Kim, In Young; Lee, Dongjoo; Choi, Min Koo; Lee, Joo Youn; Park, Seok Soon; Jeong, Seong Yun; Choi, Eun Kyung; Choi, Kyeong Sook (Cell Death and Disease, 2019)
Gambogic acid (GA), a xanthonoid extracted from the resin of the tree, Garcinia hanburyi, was recently shown to exert anticancer activity in multiple studies, but the underlying action mechanism remains unclear. Here, we show that GA induces cancer cell death accompanied by vacuolation in vitro and in vivo. This GA-induced vacuolation in various cancer cells was derived from dilation of the endoplasmic reticulum (ER) and mitochondria, and was blocked by cycloheximide. These findings suggest that GA kills cancer cells by inducing paraptosis, a vacuolization-associated cell death. We found that megamitochondria formation, which arose from the fusion of swollen mitochondria, preceded the fusion of ER-derived vacuoles. GA-induced proteasomal inhibition was found to contribute to the ER dilation and ER stress seen in treated cancer cells, and megamitochondria formation was followed by mitochondrial membrane depolarization. Interestingly, GA-induced paraptosis was effectively blocked by various thiol-containing antioxidants, and this effect was independent of ROS generation. We observed that GA can react with cysteinyl thiol to form Michael adducts, suggesting that the ability of GA to covalently modify the nucleophilic cysteinyl groups of proteins may cause protein misfolding and subsequent accumulation of misfolded proteins within the ER and mitochondria. Collectively, our findings show that disruption of thiol proteostasis and subsequent paraptosis may critically contribute to the anti-cancer effects of GA.
Keywords: Animals; Antineoplastic Agents; Antioxidants; Apoptosis; Cell Death; Cell Line, Tumor; Endoplasmic Reticulum; Endoplasmic Reticulum Stress; Garcinia; Humans; Mice; Mice, Nude; Mitochondria; Proteostasis; Reactive Oxygen Species; Sulfhydryl Compounds; Transplantation, Heterologous; Vacuoles; Xanthones